UJI FOTOSTABILITAS PIGMEN BIXIN PADA BENTONIT DAN BENTONIT TERPILAR-TiO2 - Nelly - Wahyuni (Universitas Muhammadiyah Pontianak, 2020)
One of the characteristics of the bixin pigment is its low photostability, which causes its limitations. There are many methods to improve the photostability of bixin. This study aims to study the rate of degradation of bixin in the form of an extract that will be impregnated in bentonite and TiO2 pillared bentonite. The photostability test was carried out by continuously illuminating the sample with ultraviolet (UV C) light for nine h. Bixin concentration was observed using a UV-spectrophotometer. The results showed that the impregnation of bixin extract on bentonite could increase the photostability of bixin from 14.4 h to 138.6 h. On the other, impregnation of bixin on TiO2 pillared bentonite increases the rate of bixin degradation. The half-life of bixin offered to this material is only 3.7 h. TiO2 pillared bentonite enrolls as a photocatalyst, which is enhanced photodegradation of bixin pigment. Keywords: bixin, bentonite, photostability, pigment, TiO2-pillared bentonite